Tren Penelitian Dampak Pergaulan Bebas pada Remaja - Tryas Amanda Putri; Tesa Amilia Putri; Risma Anita Puriani; Rani Mega Putri (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Teenagers, as the future generation of the nation, are facing significant challenges due to the rapid flow of globalization, technological advancements, and the weakening of social control and character education. This study aims to identify the factors contributing to the prevalence of promiscuity among teenagers, analyze its impact on social skills, and propose preventive and educational solutions. Using a literature review method, data were gathered from various relevant scientific sources published in the last five years. The results of the study show that promiscuity has negative effects on the physical and mental health, as well as the social relationships of teenagers, including teenage pregnancies, drug abuse, sexual deviation, and the decline of social skills. The minimal role of the family, the weakness of moral education, low self-control, and inadequate sex education are the main factors exacerbating this issue. On the other hand, the involvement of parents, religious education, and community-based approaches have proven effective in building the moral resilience of teenagers. The implications of this study highlight the importance of synergy between families, schools, and communities in instilling character values and equipping teenagers with healthy social skills to face the challenges of the era.